Motivasi kerja di kalangan guru sekolah - Yushawariza, Yusof (2008)
The purpose of this qualitative study was to investigate the factors that influence work motivation among teachers. This qualitative study used semi-structured interviews and participant observation. Measures were taken to ensure the credibility of the analysis and findings, such as member checking, peer debriefing, audit trail and negative case analysis. Results showed that principal's leadership, mutual collaboration among colleagues, environmental Factors, opportunities for staff development and clearly defined goals have an impact on the teachers' motivation. This qualitative study also found that the level of the teachers' motivation towards their work is at a moderate level. Principals need to use strategies to increase motivation among teachers such as providing support for teaching and learning, showing respect for teachers' abilities and opinions, providing accurate information about teaching and learning and communicating well with teachers